Identification of South Sumatra Province’s Local Wisdom as Science Literacy Objects - Sari, Widya; Wiyono, Ketang; Setyawan, Dedy; Asiandu, Angga Puja; Sa’diyah, Khalimatus; Vianita, Etna; Septialti, Delita; Sutinah, Sutinah (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2020)
The ability of Indonesian students to master physics is still low. Based on PISA in 2018, Indonesia ranked at 62th out of 72 participating countries. It was much lower than other Asian countries. Therefore, this problem should be overcome. One of the existing sources of physics literacy is local wisdom. The local wisdom can be used as a direct source of physics studies for students to increase their literacy skills. Therefore, in this paper, the authors discussed some local wisdoms in South Sumatra Province that potentially used as physics literacy objects for students in their school. South Sumatra has many local wisdoms potentially used as real objects in physics studies for students. Some of the local wisdom as otok-otok boat and roasted kemplang can be used as the object of heat transfer studies (thermal), and the traditional houses of Limas and Baghi can be used as media for learning force, mass, load and modulus of elasticity. The objects of literacy studies are sources of study that can be used by teachers in teaching physics. Through local wisdom-based literacy, it is certainly expected to improve Indonesia's PISA ranking. Not only to improve PISA ranking, but it is also increase the superiority of the nation's future generations.